Menakar Dampak KUHP dan KUHAP Baru terhadap Sistem Hukum Kesehatan di Indonesia - Alam Anbari; Dyah Ersita Yustanti (Majelis: Jurnal Hukum Indonesia, 2026)
The phenomenon of homelessness and begging in public places remains a complex social problem and impacts public order and legal norms. The main problem in this study is how the criminal law is applied to homelessness and begging in public places, and how the provisions compare in the old Criminal Code and the new Criminal Code based on Law Number 1 of 2023. This study uses a normative juridical method with a statutory approach and literature study. In the old Criminal Code, begging is regulated in Article 504 which threatens imprisonment for anyone who begs in public. Meanwhile, the new Criminal Code regulates similar acts in Article 425 which no longer uses the term "begging" explicitly, but regulates the prohibition against the repeated exploitation of certain activities in public places that disturb the community. The research results show that, despite substantial continuity, the new Criminal Code tends to use a more humanistic approach and emphasizes social rehabilitation. Law enforcement against vagrants and beggars still faces various obstacles, such as low public reporting, limited oversight by authorities, and a lack of rehabilitation facilities. Therefore, the main conclusion of this research is that a repressive approach alone is insufficiently effective. An integrated legal strategy is needed, combining penal and non-penal approaches with the active involvement of the government, the community, and social institutions.